Evaluating Zoning-Based Learning Management For Education Quality Improvement: A Case Study Of State Senior High School 24, Bandung - Moch Hary Ramdany, Hanhan (AIM: Journal of Islamic Education Management, 2023)
The primary aim of this research is to critically assess the impact of zoning-based learning management on the overall quality of education at State Senior High School 24, Bandung. Employing a rigorous and systematic approach, the study employed multiple data collection methodologies, including documentation, interviews, and observations, to gather comprehensive and in-depth insights. The findings reveal that State Senior High School 24, Bandung has demonstrated a commendable proficiency in formulating and executing effective zoning-based learning management strategies. This encompasses proficiently allocating tasks and responsibilities within the institution. Furthermore, the evaluation of the implemented zoning-based learning management approach exhibited a high level of efficacy. Through meticulous examination, both supportive and obstructive elements influencing the implementation of zoning-based learning management at State Senior High School 24, Bandung have been meticulously identified. Particularly, the study delves into the significant hindrance posed by student heterogeneity or diversity, adversely affecting the implementation process.Â